Guía técnica de mantenimiento para gabinete de protección 81A4 y plan de ejecución de pruebas a dispositivo electrónico inteligente (IED) en la bahía de línea “Reserva” de la subestación GIS 138 kV de la central Delsitanisagua, - Macas Díaz, Diego Fernando (2023)
The purpose of this degree work is establishing the standard works (SW) and preventive maintenance actions (PMA) to perform the maintenance of the electromechanical components of the line protection cabinet "81A4" of the "Reserve" bay in the GIS Substation at 138 kV of the Delsitanisagua Hydroelectric Power Plant. The research project proposes a test plan to check the operation of the intelligent electronic device (IED) MICOM P543 designed to protect overhead lines, which is associated to the protection cabinet. Field testing is performed on the MICOM P543 intelligent electronic device (IED) in the 81A4 "Reserve" cabinet by means voltage and current secondary injection with the Ponovo PW636i relay test set. Maintenance of the protection cabinets of the line bays is essential due to the safety it must provide to the protected equipment and to the personnel, as well as to maintain and preserve the installed equipment in operating conditions. In addition, the IED MICOM P543, which is integrated in the protection cabinet, undergoes a test protocol (test execution plan) defined for the execution of the maintenance tasks, with the purpose of verifying that its operation is reliable according to the needs of the Delsitanisagua substation. For this purpose, voltage and current secondary injection is carried out according to the protection schemes configured and the existing setting parameters of the protection relay. With these contributions, the GIS Substation at 138 kV of the Delsitanisagua Hydroelectric Power Plant will have a technical guide for the maintenance of the line protection cabinet 81A4 "Reserve" based on the ANSI NETA MTS 2011 standard, manufacturer's manuals and CELEC EP processes, which can be replicated in cabinets 81A1 Yanacocha2, 81A2 Yanacocha1 and 81A3 Cumbaratza. With the execution of tests to the MICOM P543 Intelligent Electronic Device (IED) of the 81A4 "Reserve" cabinet, pretend to verify its availability in order to guarantee its reliable operation in case of failure events, as well as to verify the availability of inputs, outputs and communication channels. These tests can be replicated to the Intelligent Electronic Device (IED) MICOM P543 in cabinets 81A1 Yanacocha2, 81A2 Yanacocha1 and 81A3 Cumbaratza, according to the annual maintenance plan of the line bays of the Delsitanisagua substation approved by the National Electricity Operator - CENACE. Keywords: Delsitanisagua Hydroelectric power plant, Electrical testing, Intelligent Electronic Device (IED), Ponovo PW636i, 81A4.